Tunrayo Ayinke Ayinla: The Unsung Burnish Black Glaze Wares Ceramist of Ilorin - Toyin E. Akinde (Yoruba Studies Review)
Túnráyọ̀ Àyìnkẹ́ Àyìnlá of Alámọyọ, Adéta, Ìlọrin in Nigeria is the thrust of this study. Fondly called Àyìnkẹ́ Alámọyọ in the pottery ceramics circle. Túnráyọ̀ is a burnisher extraordinaire and indeed a veteran of several decades. Madame Túnráyọ̀ Àyìnlá is unarguably one of the few Nigeria’s senior citizens still proficient in pottery practice with features in pockets of literature. Prolific as she is, it is sad to note that, her life, practice, and contribution have been masked and left unsung for too long. A vacuum this study attempts to fill; unveiling facts on her family, training, and practice. Finding revealed she is nee Àlíù, putting her training and graduation at ages eight and eighteen; coupled with over sixty (60) years of burnish black glaze culinary wares production. In conclusion, the study put Túnráyọ̀’s proficiency test and its findings hoped to place  her on the global front of burnish ceramist.